2017
DOI: 10.1051/0004-6361/201730474
|View full text |Cite
|
Sign up to set email alerts
|

TheGaia-ESO Survey

Abstract: We use Gaia-ESO Survey iDR4 data to explore the Mg-Al anti-correlation in globular clusters, that were observed as calibrators, as a demonstration of the quality of Gaia-ESO Survey data and analysis. The results compare well with the available literature, within 0.1 dex or less, after a small (compared to the internal spreads) offset between the UVES and the GIRAFFE data of 0.10-0.15 dex was taken into account. In particular, we present for the first time data for NGC 5927, one of the most metal-rich globular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
151
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(182 citation statements)
references
References 65 publications
23
151
5
Order By: Relevance
“…This was verified by Mészáros et al (2015) and by Masseron et al (2019) using the APOGEE line list, but effective temperatures and surface gravities independent of ASPCAP. Interestingly, Pancino et al (2017) have also found a similar, although slightly smaller, 0.08 dex higher metallicities than Carretta et al (2009c) in the 7 clusters in common with our sample. This latter study was carried out by the Gaia-ESO survey, completely independent of APOGEE observations and using optical spectra instead of the H-band.…”
Section: Comparisons With Literaturesupporting
confidence: 90%
See 3 more Smart Citations
“…This was verified by Mészáros et al (2015) and by Masseron et al (2019) using the APOGEE line list, but effective temperatures and surface gravities independent of ASPCAP. Interestingly, Pancino et al (2017) have also found a similar, although slightly smaller, 0.08 dex higher metallicities than Carretta et al (2009c) in the 7 clusters in common with our sample. This latter study was carried out by the Gaia-ESO survey, completely independent of APOGEE observations and using optical spectra instead of the H-band.…”
Section: Comparisons With Literaturesupporting
confidence: 90%
“…We show the four different iron scales on the top left panel of Figure 4. We find that the [Fe/H] metallicities we derive are on average 0.162 dex higher than those from the Harris catalog, 0.154 dex higher than Carretta et al (2009c), 0.064 dex higher than Pancino et al (2017).…”
Section: Comparisons With Literaturecontrasting
confidence: 62%
See 2 more Smart Citations
“…Almost all old globular clusters (GCs, older than ∼10 Gyr) are composed of multiple stellar populations (MPs). One signature of MPs is stars in GCs are not chemically homogeneous: they exhibit star-to-star variations in different elemental abundances, such as He, C, N, O, Na, Mg, Al, etc (Piotto et al 2007;Yong et al 2008;Carretta et al 2009;di Criscienzo et al 2010;Lardo et al 2012;Wang et al 2017;Pancino et al 2017;Milone et al 2019). The number of chemically enriched stars is comparable to, or greater than normal stars (Carretta et al 2009;Milone et al 2012b;.…”
Section: Introductionmentioning
confidence: 99%